2020
DOI: 10.21203/rs.3.rs-42480/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Significance of D-dimer Level in Refractory Mycoplasma Pneumoniae Pneumonia

Abstract: Background Levels of serum D-dimer (D-D) in children with mycoplasma pneumoniae pneumonia (MPP) were assessed to explore the clinical significance of D-D level in refractory MPP(RMPP). Method: A total of 430 patients with MPP were enrolled between January 2015 and December 2015, and divided into a genera MPP (GMPP) group (n = 306) and a RMPP group (n = 124). Clinical data, D-D level, white blood cell (WBC) count, C-reactive protein (CRP), blood sedimentation (ESR), and lactate dehydrogenase (LDH) were compar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As an important indicator of SMMP, ESR has been con rmed by many studies. Huang X et al found ESR was signi cantly higher in the SMPP group than those in the general MPP group (P < 0.05) [11]. Lu A et al reported that age, LDH, and ESR were the signi cant factors in predicting refractory M. pneumoniae pneumonia by logistic regression [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an important indicator of SMMP, ESR has been con rmed by many studies. Huang X et al found ESR was signi cantly higher in the SMPP group than those in the general MPP group (P < 0.05) [11]. Lu A et al reported that age, LDH, and ESR were the signi cant factors in predicting refractory M. pneumoniae pneumonia by logistic regression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also have found laboratory indicators were also related with SMMP in pediatric patients. Huang X et al reported C-reactive protein (CRP), lactate dehydrogenase (LDH) and D-dimer (D-D) as independent risk factors for SMMP, and D-D had the highest predictive power (P < 0.01) [11]. Wang M et al found that the serum concentrations of tumor necrosis factor alpha (median 114.5 pg/ml, range 49.1-897.9 pg/ml) and interferon gamma (median 376.9 pg/ml, range 221.4-1997.6 pg/ml) were signi cantly higher in children with SMMP [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation